It’s Time we Get Rid of Jury Trials - Sandeep S. Jaiswal, (Indian Journal of Social Science and Literature (IJSSL), 2024)
This paper shows that the process of jury trails are not needed in a modern society as the trial by a judge is more than enough to meet the tenets of the justice system of a fair, just, balanced, unbiased and impartial trial. We need to totally and completely abolish this giant elephant in the room from medieval ages and make the judicial process more efficient, better and quicker by introducing the trial by single judge as a norm.